Theoretical issues of investment risk: Islamic vs. conventional / Huzaimi Hussain (Universiti Teknologi MARA, Sarawak, 2005)
The objective of this paper is to analyze the theoretical issues of investment risk from both Islamic and conventional viewpoints. The major difference between the two lies mostly in the element of risk sharing, both systematic and nonsystematic. Seeking of profit/return in Islamic teaching must be confined to certain rules (ahkam) revealed in the Quran and Sunnah. Besides, Islamic Economics very much accentuates ethical business values like moderation, certainty, justice and equity.